ﺔﻴﺑﺮﻌﻟﺍ ﺔﻐﻠﻟﺍ : ﺔﺜﻳﺪﳊﺍ ﺎﻴﺴﻴﻧﻭﺪﻧﺇ ﰲ ﺎﻬﻤﻠﻌﺗﻭ ﺎﻬﻤﻴﻠﻌﺗ (ﺔﻴﺟﺫﻮﳕ ﺔﻴﻌﻗﺍﻭ ﺓﺀﺍﺮﻗ) - Dihyatun Masqon (TSAQAFAH, 2012)
This article  describes various  tricks  in  learning and  teaching Arabic  language. There are  four  important aspects:  listening, speaking,  reading and writing. These four aspects are integral language activities which are practiced simultaneously . Moreover, it is said  that there  is nothing can be spoken before  listening, there  is nothing can be read before speaking, and there  is nothing can be written before  reading. Meanwhile,  in practice, a  language learner should start with a lot of practical exercises and not use translation method. These exercises can be  in  the form of  structuring,  repeating, and communicating. However, the aspect of teacher takes very  important point. Without a good teacher, a good subject, system, and method are useless. Method is more important than subject, teacher  is more  important  than method, and the soul of the teacher  is the most  important. Beside  those, creating  a milieu  conducive  to  language  learning  is sine  qua non  and fundamental element for the  improvement of Arabic  language.